Personalizing the Care and Treatment of Alzheimer’s Disease: An Overview - Svob Strac D; Konjevod M; Sagud M; Nikolac Perkovic M; Nedic Erjavec G; Vuic B; Simic G; Vukic V; Mimica N; Pivac N (Dove Medical Press, 2021)
Dubravka Svob Strac,1,* Marcela Konjevod,1,* Marina Sagud,2,3 Matea Nikolac Perkovic,1 Gordana Nedic Erjavec,1 Barbara Vuic,1 Goran Simic,4 Vana Vukic,4 Ninoslav Mimica,5 Nela Pivac1 1Laboratory for Molecular Neuropsychiatry, Division of Molecular Medicine, Rudjer Boskovic Institute, Zagreb, Croatia; 2Department of Psychiatry, Clinical Hospital Centre Zagreb, Zagreb, Croatia; 3University of Zagreb Medical School, Zagreb, Croatia; 4Department of Neuroscience, Croatian Institute for Brain Research, Zagreb, Croatia; 5Clinics for Psychiatry Vrapce, Zagreb, Croatia*These authors contributed equally to this workCorrespondence: Nela PivacLaboratory for Molecular Neuropsychiatry, Division of Molecular Medicine, Rudjer Boskovic Institute, Bijenicka Cesta 54, Zagreb, 10 000, CroatiaTel +385 1 4571 207Fax +385 1 456 1010Email npivac@irb.hrAbstract: Alzheimer’s disease (AD) is a progressive, complex, and multifactorial neurodegenerative disorder, still without effective and stable therapeutic strategies. Currently, available medications for AD are based on symptomatic therapy, which include acetylcholinesterase (AChE) inhibitors and N-methyl-D-aspartate (NMDA) receptor antagonist. Additionally, medications such as antipsychotic drugs, antidepressants, sedative, and hypnotic agents, and mood stabilizers are used for the management of behavioral and psychological symptoms of dementia (BPSD). Clinical research has been extensively investigated treatments focusing on the hallmark pathology of AD, including the amyloid deposition, tau hyperphosphorylation, neuroinflammation, and vascular changes; however, so far without success, as all new potential drugs failed to show significant clinical benefit. The underlying heterogeneous etiology and diverse symptoms of AD suggest that a precision medicine strategy is required, which would take into account the complex genetic, epigenetic, and environmental landscape of each AD patient. The article provides a comprehensive overview of the literature on AD, the current and potential therapy of both cognitive symptoms as well as BPSD, with a special focus on gut microbiota and epigenetic modifications as new emerging drug targets. Their specific patterns could represent the basis for novel individually tailored approaches aimed to optimize precision medicine strategies for AD prevention and treatment. However, the successful application of precision medicine to AD demands a further extensive research of underlying pathological processes, as well as clinical and biological complexity of this multifactorial neurodegenerative disorder.Keywords: Alzheimer disease, therapy, precision medicine, gut microbiota, epigenetics